Multiple Criteria Preference Relation by Dominance Relations in Soft Set Theory - Awang, Mohd Isa; Mohd Rose, Prof. Madya Dr. Ahmad Nazari; Ahmad, Prof. Madya Dr. Fadhilah; Awang, Prof. Madya Ts. Dr. Mohd Khalid (Springer International Publishing, 2016)
This paper presents the applicability of soft set theory for discovering the preference relation in multi-valued information systems. The proposed approach is based on the notion of multi-soft sets. An inclusion of objects into value set of decision class in soft set theory is used to discover the relation between objects based on preference relation. Results from the experiment shows that dominance relation based on soft theory for preference relation is able to produce a finer object classification by eliminating inconsistencies during classification process as opposed to the expert judgement classification.